Alcohol dependence and the psychological factors leading to a relapse: a hospital-based study in Vietnam - Nhat Van Trieu; Penpaktr Uthis; Sunisa Suktrakul (College of Public Health Sciences, Chulalongkorn University, 2021)
Purpose - To study the situation of alcohol relapse and to investigate the relationship between psychological factors and alcohol relapse in persons with alcohol dependence in Thai Nguyen hospitals, Vietnam. Design/methodology/approach - A correlation study was conducted among 110 patients. Data were collected through structured interviews and were analyzed using descriptive statistics and Spearman's correlation coefficient (rs). Findings - More than two-thirds of the participants were found to relapse more than once (X̅ = 2.04, SD = 0.86). Positive outcome expectancies, cravings, negative emotional states, and maladaptive coping were positively associated with relapse (rs = 0.550, 0.522, 0.497; p = 0.000 and rs = 0.217, p < 0.05, respectively). While, motivation to change with three subscales had a negative correlation to relapse including recognition (rs = −0.199, p < 0.05), ambivalence (rs = −0.331, p = 0.000), and taking steps (rs = −0.606, p = 0.000). Adaptive coping, self-efficacy, and social support were also found to be negatively correlated to relapse (rs = −0.535, −0.499, −0.338; p = 0.000, respectively). However, negative outcome expectancies (rs = −0.024, p = 0.805) and positive emotional states (rs = 0.081, p = 0.399) were not significantly related to relapse. Practical implications - The findings of this study are significant implications for relapse prevention strategies. It suggests that the essential parts of relapse prevention are through: changing alcohol expectations, increase drinking refusal self-efficacy, coping skills training, enhancing motivation to change, managing alcohol craving and expanding social support. Originality/value - This is the first study in Vietnam which investigated the relationship between psychological factors and alcohol relapse in individuals with alcohol dependence.